A Novel -Inspired Routing Protocol for Wireless Sensor Networks - Mingchuan Zhang; Changqiao Xu; Jianfeng Guan; Ruijuan Zheng; Qingtao Wu; Hongke Zhang (International Journal of Distributed Sensor Networks)
There is a tradeoff between routing efficiency and energy equilibrium for sensor nodes in wireless sensor networks (WSNs). Inspired by the large and single-celled amoeboid organism, slime mold Physarum polycephalum , this paper presents a novel Physarum -inspired routing protocol (P-iRP) for WSNs to address the above issue. In P-iRP, a sensor node can choose the proper next hop by using a proposed Physarum -inspired selecting next hop model (P-iSNH), which comprehensively considers the distance, energy residue, and location of the next hop. As a result, the P-iRP can get a rather low algorithm complexity of O ( n ) , which greatly reduces the processing delay and saves the energy of sensors. Moreover, by theoretical analysis, the P-iSNH always has an equilibrium solution for multiple next hop candidates, which is vital factor to the stability of routing protocol. Finally, simulation results show that P-iRP can perform better in many scenarios and achieve the effective tradeoff between routing efficiency and energy equilibrium compared to other famous algorithms.